Interferensi Afiks Serapan Bahasa Asing Ke Dalam Bahasa Indonesia: Analisis Perspektif Sosiolinguistik - Salman Khairy Farras (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This article discusses the interference of foreign language absorption affixes to Indonesian from a sociolinguistic perspective. The discussion will be presented in the form of data analysis using qualitative research methods. This study uses a sociolinguistic approach to determine the process of forming absorption affixes in social interactions. Therefore, this article will present a theoretical study of the process of absorption of foreign affixes and their use in written and oral varieties. The results of this study indicate that there are several affixes that are absorbed immediately by the speakers in the process of social interaction. Thus, a discussion on the absorption of foreign affixes into Indonesian from a sociolinguistic perspective can enrich scientific treasures at the morphological level and their relevance to life.